Enhanced oil recovery with anionic and zwitterionic surfactants in carbonate rocks: A CT-aided investigation. (1st March 2022) - Chen, Xiongyu; Sotomayor, Mauricio; Alshaer, Hassan J.; Song, Haofeng; Panthi, Krishna; Balhoff, Matthew; Mohanty, Kishore K.
Graphical abstract: Highlights: The zwitterionic – anionic surfactants synergy at oil/water interface gives ultralow IFT. A small amount of oil in the surfactant/polymer solution improves aqueous stability. A negative correlation of oil saturation (So ) vs. porosity in mixed-wet carbonates. A positive correlation of non-aqueous phase saturation vs. porosity in sandstones. The zwitterionic – anionic blend reduces So to 10% by draining oil in pores ≥200 nm. Abstract: Surfactant-polymer enhanced oil recovery (EOR) in carbonates is challenging at high salinity/hardness and high temperature conditions due to poor aqueous stability at these conditions. This work finds that a surfactant blend of zwitterionic surfactant (lauryl betaine) and anionic surfactants (carboxylate & internal olefin sulfonate – IOS) that is aqueous stable at 4–6 wt% salinity and 100 °C and has ultralow water/oil interfacial tension (IFT) to allow near-miscible water/oil displacement to enhance oil recovery. The surfactant-polymer aqueous stability is greatly improved after mixing 2 wt% oil to create a homogeneous oil-in-water microemulsion. Flow experiments are conducted at 100 °C in Indiana limestone cores with vugs and microporosity. The zwitterionic-anionic surfactant blend reduces oil saturation to 10% and drains oil in pores ≥200 nm. In comparison, the anionic blend (carboxylate + IOS) reduces oil saturation to 23% and drains oil in pores ≥1 μm. The adsorption of both surfactant blends on carbonate is less than 0.4 mg/g. Particularly, the X-ray computed tomography (CT) images show a negative correlation between pixel-wise oil saturation and porosity during oil displacements by water and by surfactant/polymer. This correlation is likely due to capillary pressure and the mixed wettability of the Indiana limestone. These results provide new surfactant formulations for EOR at extreme conditions and insights for modeling EOR in rocks with porosity heterogeneity and mixed-wettability.